Kajian tentang faktor-faktor yg mempengaruhi tingkah laku selamat dalam kalangan pekerja kontraktor di sektor pembuatan - Subki, Ahmad (2017)
Model 50-item Work Safety Scales (WSS) which developed by Hayes et al. (1998) was adopted to investigate the influence of the five facets of WSS on compliance with safety behaviour among contractors in manufacturing sector. The survey was done among 130 respondents (112 questionnaires were returned back) by using a questionnaire which measures the workers’ perceptions on job safety, coworker safety, supervisor safety, management safety, and satisfaction with safety program towards compliance with safety behaviour. All the results were then analyzed statistically with descriptive analysis of respondents’ background, reliability tests on variables’ internal consistencies, correlation, and regression analysis. The findings showed that the most significant facets were the satisfaction with safety program and coworker safety in predicting the relation to comply with safety behaviour. The job safety and supervisor safety, however, indicated negative relationship to the compliance with safety behaviour. The management safety was non-significant to the compliance with safety behaviour in this study. The findings would be valuable guidance to researchers to help the organization work on the level of compliance with safety behaviour.